Recovery and Treatment of Solid Waste (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The recovery of solid waste is a challenge and an opportunity for companies, thanks to the ongoing awareness of sustainability and technological advances. The end-of-waste criteria constitute a European strategic goal that promotes recycling in order to ensure a high level of environmental protection by means of reducing the quantity of waste destined for disposal. This Special Issue promotes the knowledge regarding technological methods for solid waste recovery. Articles investigate innovative processing methods with the goal of valorizing solid waste from different civil and industrial activities. Topics includes studies on construction and building, mining, plastics, and WEEE, referring to the treatment techniques used and, where appropriate, the critical raw materials that can be valorized. The recovery processes of critical raw materials can be very energy-intensive, affecting environmental and soil factors. Case studies on sustainable, low-carbon and resource-efficient techniques for the purpose of a more competitive economy were also very welcomed. The environmental impact and safety measures, especially for dangerous waste, should be taken into account in the description of their processing and management.